Re-evaluation of the genus Biapertura Smirnov, 1971 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2020)
The genus Biapertura Smirnov, 1971, with type species B. affinis (= Lynceus affinis Leydig, 1860) is re-evaluated, removing the affinis-group from polyphyletic Alona s. lato. Biapertura s. str. is a taxon which could be defined by large size (up to 1.1 mm), having head shield with triangular posterior portion and two connected major head pores, and by having massive postabdomen with over 10 well-developed composite marginal denticles and well-developed lateral fascicles of setulae. Thoracic limbs of Biapertura are of Hexalona-type, inner distal lobe of limb I bear extremely large, usually claw-like seta 1. Australian species of the genus, B. kendallensis (Henry, 1919) and B. elliptica (Sinev, 1997), are fully redescribed here. Morphological analysis suggests that Biapertura s. str. is a sister-group to Alona s. str. A key to seven species of the genus is provided and a discussion of their geographic distribution and habitat type is given.